Pengaruh Penerapan Ice Breaking Terhadap Motivasi Belajar Pendidikan Agama Kristen Dan Budi Pekerti Kelas VII SMP Negeri 1 Sitio Tio Kabupaten Samosir Tahun Pelajaran 2023/2024 - Pevrina Sitanggang; Simion D. Harianja; Oktober Tua Aritonang; Risden Anakampun; Robinhot Sihombing (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this research is to determine the effect of implementing Ice Breaking on the learning motivation of Christian Religious Education and Character Education for class VII students at SMP Negeri 1 Sitio Tio, Samosir Regency, Academic Year 2023/2024. The method in this research is a pre-experimental design research method in the form of